Design of Portable Nano-hydro Generator for Lighting in Mountain Areas - Gurum Ahmad Pauzi; Muhammad Ridwan; Amir Supriyanto; Sri Wahyu Suciyati (Journal of Energy, Material, and Instrumentation Technology, 2022)
Electricity needs in mountainous areas have not been optimal, so there need to be alternative power plants to meet the electricity supply in the mountainous area. For this reason, this study made an alternative power plant tool with the title Nano-hydro Generator Design Easy to Carry For Lighting In Mountainous Areas. The creation of this tool has several stages, including the first stage of making graphic design through SketchUp applications, then the second stage of the tool assembly in the form of mechanical design and civilian build, then the third stage of testing tools through water media, and the last stage of data retrieval to see if this tool works optimally. Based on the results of trials and data collection obtained, the average rotation speed of the turbine of 48.6 rpm, the rotation speed of the generator of 194.3 rpm, and a voltage of 6.3 volts.